L'urgence au sein de la justice des mineurs : un exemple de la dé-temporalisation de l'intervention sociale - Marc Bessin (Sociétés et Jeunesses en Difficulté)
Emergencies in the juvenile justice system : an example of de-temporalisation of social work intervention                       This article deals with temporality in judicial practices in relation to a general tendency of reduction of temporal horizons and towards “de-temporalisation”, that is a difficulty in seeing present action in relation to the past and with regard to of the future. The educational time of juvenile justice has specific attributes and takes place over a long period. Child judges expect that measures will be of long duration and this time scale is considered as reversible and modifiable, in order to adapt their intervention as function of the evolution of the family. A French nationwide study of emergency child placements enables the author to confirm that judges are going back to traditional legalistic approaches and that the educational concept of juvenile justice is being eroded. As a way of anticipating on the risks run by minors in danger, in a socio-political context where action in the present time is valued to the detriment of an overall temporal perspective, the author shows how procedures for emergencies have been institutionalised, thus leaving aside the longer term educational time perspective.